Review of a decade of fauna research in Côte d'Ivoire with insights into wildlife health and zoonotic transmissions - Dindé, A.O.; Cook, Elizabeth A.J.; Terfa, Zelalem; Soro, D.; Hung Nguyen-Viet; Bett, Bernard K.; Bonfoh, B. (Elsevier, 2025)
Côte d'Ivoire has a strong relationship with wildlife, demonstrating both a commitment to conservation and a persistent wild animal products value chain. Given the increasing global risk of pathogens spillover and zoonotic disease transmission and the role of wildlife in this process, the current review examines studies on wildlife conducted in Côte d'Ivoire and published between 2012 and 2022. Focusing on wildlife health and pathogens, it analyzes research trends, identifies gaps and highlights perspectives for improving wildlife-human interactions to prevent zoonotic risks. Findings indicate that wildlife research in Côte d'Ivoire has expanded in recent years but remains discipline-specific, primary focused on conservation, with notable geographical and species-related disparities. While a wide range of pathogens has been studied, significant gaps persist in understanding pathogen dynamics at human-wildlife interfaces and the potential risks of spillover. There is a critical need for more integrated research and comprehensive surveillance in wildlife, particularly targeting species that frequently interact with humans at the buffer zones and through wild meat consumption. Surveillance efforts, especially in high-risk regions will be essential to anticipate and prevent emerging health threats.